Influence mechanism of digital economy development on the supply efficiency of ecological products - Shao, Jingbo (Frontiers in Environmental Science, 2024)
Improving the supply efficiency of ecological products (EPSE) is of great significance to protect the ecological environment, promote the development of green industry and the sustainable growth of the economy. Based on this, this paper constructs an evaluation index system for the EPSE and uses the Undesirable Slacks-Based Measurement (SBM) Model to measure the EPSE in 30 provinces (cities and districts) in China from 2011 to 2022. On this basis, the spatial econometric model, panel threshold effect model and other methods are used to innovatively explore the impact mechanism and non-linear relationship between the development level of the digital economy (DE) in 30 provinces and cities in China on the EPSE. The research shows that: (1) From the calculation results of the EPSE, the overall level of EPSE in the study area is not high, and the development difference is significant; (2) From the results of spatial econometric regression, The DE has a significant spatial spillover effect on the EPSE, and in neighboring areas is significantly negative; (3) From the analysis of the impact mechanism, the development of the DE promotes the EPSE by upgrading the human capital structure, upgrading the industrial structure, and increasing local government fiscal revenue and corporate operating profits; (4) From the perspective of heterogeneity analysis, the impact of DE on the EPSE has significant heterogeneity in eastern, central and western China, among which the positive impact on the eastern and western regions is significant; (5) From the regression results of the threshold effect, there is a significant single threshold effect on the impact of the development level of the DE on the EPSE. When the threshold value is less than 0.1232, The DE will significantly promote the improvement of the EPSE. This paper provides new literature evidence and factual reference for the causal relationship between the DE and the EPSE.